1959
DOI: 10.1071/mf9590007
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption of Phosphate by Estuarine Bottom Deposits

Abstract: Experiments were made on the effects of pH, phosphate concentration, particle size, iron, and organic matter on the adsorption of phosphate by estuarine bottom deposits in as natural a state as possible. Measurements of the ability of the silt to adsorb phosphate were made by isotope dilution, using 32P. The silt was separated into four fractions by sedimentation. The ability of silts to adsorb phosphate was directly related to the ratio of their contents of iron to organic matter. Organic matter depressed pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1962
1962
1993
1993

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Several investigators have emphasized the significance of Fe and its hydrous oxides to the precipitation and sorption of P (Mortimer 1941;MacPhcrson et al 1958;Jitts 1959). F cwer investigators have emphasized the role of hydrous Mn oxides as a sorptivc complex for P fixation; Mackereth (1966) attributed the maximum sedimcntary concentrations of phosphorus in Windermerc and Esthwaite Water in England to the high efficiency of coprecipitation of P with Fe and Mn compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have emphasized the significance of Fe and its hydrous oxides to the precipitation and sorption of P (Mortimer 1941;MacPhcrson et al 1958;Jitts 1959). F cwer investigators have emphasized the role of hydrous Mn oxides as a sorptivc complex for P fixation; Mackereth (1966) attributed the maximum sedimcntary concentrations of phosphorus in Windermerc and Esthwaite Water in England to the high efficiency of coprecipitation of P with Fe and Mn compounds.…”
Section: Resultsmentioning
confidence: 99%
“…61 In a study of estuarine bottom sediments, it was concluded that the silt would act continuously as a trap of phosphate at the expense of overlying water especially during the run-off cycle. 60 Apparently there is no proven relationship between the ability of sediments to adsorb added phosphate and the trophic state of a lake. 57 Accordingly, it was concluded that the factors controlling eutrophication are evidently complex.…”
Section: Ox = (\Ibx M ) + Cix Mmentioning
confidence: 98%
“…However, it has been reported that the phosphate adsorption capacity of two Australian estuarine sediments was dependent on their Fe/organic matter ratio; the content of the latter depressing adsorption. 60 On the other hand, Shukla et al believe that the effect of organic P on phosphate adsorption has not been established definitely. 49 The phosphate adsorbed from dilute solution by the sediment of a Connecticut eutrophic lake seemed to be tightly bound unlike the additional loosely-bound phosphate adsorbed from more concentated solutions (> 1 mg P g" 1 of sediment).…”
Section: Ox = (\Ibx M ) + Cix Mmentioning
confidence: 98%
“…In these waters, phosphate concentrations are controlled through an interaction with suspended sediments as demonstrated by the constancy of dissolved phosphate levels when suspensions of river or estuarine sediments are diluted with distilled and/or sea water, (Stephens-en, 1949;Rochford, 1951;Carritt & Goodgal, 1954;Jitts, 1959;Gessner, 1960;Pomeroy etal., 1965;Burns and Solomon, 1969;Butler and Tibbits, 1972;Wormald and Stirling, 1979;Chase and Sayles, 1980;Fox et al, 1985Fox et al, , 1986. This control appears to be the result of binary exchange between phosphate and amorphous ferric hydroxide in suspension or as surface coatings on suspended sediments (Fox, 1989(Fox, , 1990(Fox, , 1991.…”
Section: Model Developmentmentioning
confidence: 99%